Training method and arm strength interactions in novice table tennis skill development: A factorial study - Langitan, Fentje; Baan, Addriana Bulu; Podungge, Risna (UIR Press, 2025)
Background: Developing proficiency in the backhand drive is essential for novice table tennis players, yet identifying the most effective training methodologies remains a significant challenge. However, existing literature has predominantly examined training methods in isolation. There is a notable lack of empirical evidence regarding how these methods interact with individual physical attributes, leading to a potential gap in understanding effective personalized coaching strategies. Objectives: This study aimed to examine the interaction between two common training methods (wall bounce vs. pairing) and arm muscle strength (strong vs. weak) on the acquisition of backhand drive skills in novice players. Methods: A 2 × 2 factorial experimental design was employed over an eight-week period with 76 novice male university students (age 18-22). Participants were stratified into four groups based on the training method and arm muscle strength, which was assessed using a 30-second push-up test. Backhand drive ability was evaluated using a validated scoring rubric. Finding/Results: A two-way ANOVA revealed a significant main effects for training method (p < .043, ηp2 ​= 0.11) and arm muscle strength (p < .001, ηp2​ = 0.70), as well as an interaction effect between these factors on backhand drive performance (F(1.36) = 6.99, p < .05, ηp2​ = 0.16). Post-hoc analysis showed that the wall bounce method was significantly more effective for players with strong arm muscles (p < .05), whereas for players with weaker arm muscles, no significant difference was found between the two training methods (p > .05). Conclusion: The optimal training method for backhand drive development is contingent on the athlete's physical characteristics. This finding challenges the one-size-fits-all coaching paradigm and provides strong evidence for a personalized approach that matches training methodologies to the individual strength levels of athletes.